2020
DOI: 10.3389/fphar.2020.01210
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Berberine-Based Chinese Medicine Assembled Nanostructures on Diarrhea-Predominant Irritable Bowel Syndrome In Vivo

Abstract: Diarrhea-predominant irritable bowel syndrome (IBS-D) is one common chronic functional disease of the digestive system with limited treatments. The microbiota–gut–brain axis (MGBA) has a central function in the pathogeny of IBS-D, which includes the participation of many various factors, such as brain-gut peptides (BGPs), immune inflammation, and intestinal flora. Inspired by the drug combination in traditional Chinese medicine (TCM), our previous study discovered that berberine (BBR) and baicalin (BA) could f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 35 publications
1
46
1
Order By: Relevance
“…This genus is also rich in pharmacologically active compounds, such as berberine, berbamine, palmatine, oxyacanthine, and jatrorrhizine [52]. Berberine is widely used to treat diarrhea by inhibiting intestinal inflammation and regulating intestinal bacteria [53][54][55][56][57].…”
Section: Important Plant Usesmentioning
confidence: 99%
“…This genus is also rich in pharmacologically active compounds, such as berberine, berbamine, palmatine, oxyacanthine, and jatrorrhizine [52]. Berberine is widely used to treat diarrhea by inhibiting intestinal inflammation and regulating intestinal bacteria [53][54][55][56][57].…”
Section: Important Plant Usesmentioning
confidence: 99%
“…Irritable bowel syndrome (IBS) is one of the most common functional gastrointestinal diseases with no organic pathological changes that can explain its symptoms, and its incidence is about 10–20% worldwide ( Rusu and Dumitrascu, 2015 ). Diarrhea-predominant irritable bowel syndrome (IBS-D) is one of the most important phenotypes of IBS, with recurrent abdominal pain and diarrhea as the main clinical manifestations ( Li et al, 2020 ). At present, most scholars believe that IBS-D is the result of multiple factors.…”
Section: Introductionmentioning
confidence: 99%
“…Both of the MyD88-dependent pathway and NF- κ B independent pathway play a pivotal role in TLR4 signal transduction. Meanwhile, NF- κ B plays an important role in a variety of stress diseases, such as neurodegenerative diseases, as a key regulatory factor through dynamic nuclear DNA/protein binding [ 25 , 26 ]. This study found that the expression levels of MyD88 and NF- κ B in the QingHuaZhiXie prescription group were significantly lower than those in the D-IBS group, indicating that QingHuaZhiXie prescription can act on the two signal transduction pathways of TLR4 at the same time, thus preventing the subsequent inflammatory reaction.…”
Section: Discussionmentioning
confidence: 99%